Impact of a Complete Systematic Land Registration Program (PTSL) Against the Regional Economy in Deli Serdang Regency - Susi Adila Sari; Marlon Sihombing; Agus Purwoko (Sekolah Pascasarjana Universitas Brawijaya, 2019)
This study aims to analyze the impact of the implementation of a Complete Systematic Land Registration program (PTSL) in the economy of the Deli Serdang Regency of North Sumatra Province. The study sample consisted of 100 respondents who attended the Complete Systematic Land Registration (PTSL) program. The data collection methods used were Observation, Questionnaire and Documentation. The research method used is Quantitative with Z Test data analysis which is looking at income before and after the Complete Systematic Land Registration Program (PTSL). The results showed that the Complete Systematic Land Registration Program (PTSL) was able to open up opportunities for the community to obtain loans for venture capital. This indicated that there was an increase in business capital before and after the Complete Systematic Land Registration Program (PTSL) in Deli Regency National Land Agency Serdang. The results of the analysis and discussion that have been conducted show a significant increase in income through the Complete Systematic Land Registration program which also affects the regional economy in Deli Serdang.